The murders. Season 1 [videorecording (DVD)] - Lucas, Jessica, 1985-; Bruce, Dylan, 1980-; Chen, Terry (Sundance Now, 2021)
Jessica Lucas stars in this Canadian mystery series as Kate Jameson, a rookie detective determined to make her mark on the homicide team. But things go horribly awry when she breaks the first rule of policing: never leave your gun unattended. Haunted by her mistake, Kate seeks to make amends through every case, including that of a mysterious killer who seems particularly invested in her.